Bologna dopo la pandemia Impatto territoriale e scenari futuri - Castrignanò, Marco; RIMONDI, TOMMASO (Sociologia del territorio, 2023)
Covid-19 has dramatically shown some of the limits of our cities. Labor market, tourism, service sector have suffered a backlash that can be read as an "explosion" of pre-existing inequalities. The slow and progressive process of recovery we are experiencing let us talk about a "post-Covid" phase, characterized by a forced coexistence with the coronavirus and its mutations, while the health emergency still affects the organization of urban life. Adopting a multidisciplinary perspective, this book provides a wide reflection on the multifaceted impacts of the pandemic on the city of Bologna. On the one hand, the chapters show how people are not "all on the same boat" in the pandemic context, with pre-existing inequalities and other vulnerabilities contributing to determine different individual experiences and outcomes. On the other hand, many authors illustrate how the socio-economic fabric of the city has given proof of resilience, with new perspective of social and territorial development in the fields of technological innovation and sustainable mobility.